Design and planning of energy supply chain networks. - Murele, Oluwatosin Christiana (Cranfield University, 2019)
During a period of transformation towards decarbonised energy networks, maintenance of a reliable and secure energy supply whilst increasing efficiency and reducing cost will be key aims for all energy supply chain (ESC) networks. With the knowledge that about 80% of global energy is obtained from fossil fuels, appropriate design and planning of its supply chain networks is inevitable. Notwithstanding, renewable energy sources, such as biomass, solar, wind and geothermal, will also play important roles in the future ESCs as climate change mitigation becomes an increasingly important concern. To achieve this aim, energy systems optimization models were derived; (i) for the simultaneous planning of energy production and maintenance in combined heat and power (CHP) plants for overall cost reduction, with results obtained benchmarked against data from industry; (ii) for biomass integration into ESC networks for emissions reduction and benchmarking it against data from literature and the governing equations solved for optimality using the General Algebraic Modelling System (GAMS) software. Further, energy survey questionnaires were developed using the Qualtrics online survey tool and same disseminated to individuals in some counties of the United Kingdom (UK) with the aim of proposing strategies for improved renewable energy (RE) embracement in the UK energy mix. The case study of the coal-fired CHP plant predicted a 21% reduction in annual total cost in comparison to the implemented industrial solution that follows a predefined maintenance policy, thereby, enhancing the resource and energy efficiency of the plant. Additionally, the optimization model for integrating biomass into energy supply chain networks indicated that a reduction in the emissions level of up to 4.32% is achievable on integration of 5-8% of biomass in the ESC with a 4.57% increase in the total cost of the ESC network predicted at biomass fraction of 7.9% in the mixed fuel, indicating that the cost increment in a biomass and coal co-fired plant can be offset with the introduction of effective carbon pricing legislation.
Keywords: energy networks; renewable energy sources; energy systems optimization; combined heat and power (CHO) plants; optimization model; climate change mitigation